2018
DOI: 10.1103/physrevb.97.235411
|View full text |Cite
|
Sign up to set email alerts
|

Tunable transmittance in anisotropic two-dimensional materials

Abstract: A uniaxial strain applied to graphene-like materials moves the Dirac nodes along the boundary of the Brillouin zone. An extreme case is the merging of the Dirac node positions to a single degenerate spectral node which gives rise to a new topological phase. Then isotropic Dirac nodes are replaced by a node with a linear behavior in one and a parabolic behavior in the other direction. This anisotropy influences substantially the optical properties. We propose a method to determine characteristic spectral and tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Both depend on the material parameters of mass m and velocity v defining the Hamiltonian. Our formulas agree with results presented in the very recent paper of Nualpijit et al 43 . As noted in that paper, the above material parameters cancel out of the square root of the product σ xx inter (Ω)σ yy inter (Ω) and consequently this quantity is universal and constant as in graphene, independent of photon energy.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Both depend on the material parameters of mass m and velocity v defining the Hamiltonian. Our formulas agree with results presented in the very recent paper of Nualpijit et al 43 . As noted in that paper, the above material parameters cancel out of the square root of the product σ xx inter (Ω)σ yy inter (Ω) and consequently this quantity is universal and constant as in graphene, independent of photon energy.…”
Section: Introductionsupporting
confidence: 92%
“…The anisotropy of the semi-Dirac model, which is not part of the pure Dirac case, has other consequences. For instance, the transmittance as a function of incident polarization angle 43 is altered in an important way, as is the dichroism 44 . Another discussion of the effect of anisotropy on transport and other properties was given by Sriluckshmy et al 45 .…”
Section: Introductionmentioning
confidence: 99%
“…Hamiltonian (6) coincides with the Hamiltonian of the Dirac theory on 2d random surfaces induced from 3d flat Dirac theory with an Euclidean metric defined in Refs. [15,16].…”
Section: Introductionmentioning
confidence: 73%
“…The physics of electronic properties of strained [1][2][3][4][5][6] or lattice deformed graphene [10][11][12][17][18][19]] is an interesting problem, which reveals how concepts of 2d gravity can penetrate into the condensed matter area. Usually, one argues that deformations and strains give rise to the curvature of the surface of a 2d crystal, which is equivalent to the presence of gravity in a twodimensional world [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike most Dirac materials that possess liner dispersions in all momentum-space directions [3][4][5], in SDMs the low-energy excitations disperse quadratically in one direction but linearly along the orthogonal direction [6][7][8][9][10]. The unique band structures of SDMs are responsible for a series of novel phenomena [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], including the consequences of anisotropic aspect in the superconducting order parameter correlations [25][26][27]. Recent theoretical efforts have demonstrated that the superconductivity in SDMs can be induced by arbitrarily weak attractions in the present of random chemical potential [25].…”
Section: Introductionmentioning
confidence: 99%